Diagenetic Features and Porosity Development for Hartha Formation in the Balad and East Baghdad Oil Fields, Central Iraq - Ismial, Aliya Sadoon; Nasser, Midhat E.; Al-Sharaa, Ghazi H. (Iraqi Journal of Science, 2022)
The Hartha Formation (age Late Campanian – Early Maastrichtian) is considered an important oil reservoir in Iraq. The petrography and the diagenetic features were determined based on the analyses of 430 thin sections from selected wells within Balad and East Baghdad oil fields, Ba-2, Ba-3, EB-53, Eb-56 and EB-102. The most important and common diagenesis processes that affect Hartha Formation include Cementation, Neomorphsim, Micrtitization, Dolomitization, Compaction, Dissolution, and Authigenic minerals. This diagenesis deformation on Hartha Formation has overall accentuated the reservoir quality heterogeneity. The reservoir quality evolution is affected by destruction by grain compaction mechanical and chemical (stylolitization) causing decreases in porosity and permeability. The porosity is continuous through stylolite and is affected by dissolution precedes between the stylolite walls. The permeability decreased due to cementation. These processes led to seven proximately heterogeneity units in the Hartha Formation, characterized by a decrease in their porosity as barrier units of the Balad Oil Field. While in the East Baghdad oil field the effective porosity units appeared with less thickness of the barrier unit. The reservoir quality enhancement has resulted from dissolution, recrystallization, and partial dolomitization appeared alternately with the barrier unit in the upper part of Hartha Formation of Balad and Baghdad Oil Fields.